PERLINDUNGAN HUKUM TERHADAP PEMUSNAHAN BARANG PRIBADI MILIK TERDAKWA BERUPA MATA UANG ASING (STUDI PUTUSAN NOMOR: 2804/PID.B/2022/PN.SBY) - Ardiansyah, Rizal Firman; Cornelis, Vieta Imelda (Gapenas Publisher, 2025)
Destruction of evidence usually occurs in drug cases such as narcotics, illegal drugs, traditional medicines without distribution permits, alcoholic drinks, and sharp weapons whose ingredients are very dangerous to the public. Legal findings which constitute injustice in the decision given to the defendant in the form of confiscation of assets. individuals in the form of foreign currency denominations that will be destroyed, which basically means the destruction of foreign currency denominations, and there is no legal product that regulates this matter. This research was designed using doctrinal legal research or normative law which analyzes library sources and secondary data. Includes legal approaches, conceptual approaches, and case study approaches which are useful for identifying legal products, legal principles, and legal concepts as the basis for answers to the legal problems faced. The findings of this research are that the judge issued a decision/decision against the defendant by only looking at it from a normative perspective without involving a sense of justice and applicable legal values. Therefore, the legal protection that can be carried out by the defendant and his legal representatives is appeal and cassation. So that the defendant's rights to his personal property can be restored.